2019
DOI: 10.1017/s0950268819001353
|View full text |Cite
|
Sign up to set email alerts
|

Are there missed opportunities for vaccinating against hepatitis B among people who inject drugs in the UK?

Abstract: Sustaining the impact of hepatitis B virus (HBV) vaccination on incidence and prevalence of HBV infection requires increasing and maintaining the uptake of vaccine among those at risk. In recent years, the level of vaccine uptake among people who inject drugs (PWID) in the UK has levelled-off. Data (2015–2016) from the national unlinked-anonymous monitoring survey of PWID, an annual survey that collects data from PWID across England, Wales and Northern Ireland, were used to examine HBV vaccine uptake. Data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Our study also found that hepatitis B vaccination is associated with exposure to accurate information related to hepatitis B infection, and the benefits of vaccination as one of the most effective preventive methods. Although information about hepatitis B and vaccination is available through the media, such as television, scientific magazines, and the internet [ 43 ], Njoroge et al found that direct information from health providers was most closely associated with being vaccinated for hepatitis B [ 44 ]. However, some studies found that knowledge of hepatitis B and vaccination among health care workers is low [ 28 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that hepatitis B vaccination is associated with exposure to accurate information related to hepatitis B infection, and the benefits of vaccination as one of the most effective preventive methods. Although information about hepatitis B and vaccination is available through the media, such as television, scientific magazines, and the internet [ 43 ], Njoroge et al found that direct information from health providers was most closely associated with being vaccinated for hepatitis B [ 44 ]. However, some studies found that knowledge of hepatitis B and vaccination among health care workers is low [ 28 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…groups of people with a certain migrational background) cannot be derived from these samples. Many of the studies obtained data on vaccination status from self-reports, which have low validity and lead to an overestimation of VC (86,(89)(90)(91). Also, results obtained from serology without further information on past immunisation only provide information on a current titre.…”
Section: Discussionmentioning
confidence: 99%